2011
DOI: 10.1007/s10620-011-1886-5
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Survey of the Management After Gastric Endoscopic Submucosal Dissection Related to Postoperative Bleeding

Abstract: Post-ESD management (duration of PPI use, resumption of food intake, and performance of second-look endoscopy) varied among the medical centers; thus, randomized controlled trials are required for an optimal strategy after gastric ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 18 publications
3
74
2
2
Order By: Relevance
“…after second-look endoscopy were not significantly different (4,5). In our study, however, more delayed bleedings occurred before second-look endoscopy than after (p=0,022).…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…after second-look endoscopy were not significantly different (4,5). In our study, however, more delayed bleedings occurred before second-look endoscopy than after (p=0,022).…”
Section: Discussioncontrasting
confidence: 61%
“…Most hospitals routinely perform a second-look endoscopy to check for delayed bleeding, though there is little solid evidence to support this practice. Two reports have suggested that a second-look endoscopy after gastric ESD does not contribute significantly in the prevention of delayed bleeding (4,5). However, this has been held true in our experience.…”
Section: Introductioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Antithrombotic drugs and low-dose aspirin were discontinued in all patients who resumed oral ingestion following endoscopic hemostasis, and there were no deaths or complications due to withdrawal. Recent reports in Japan, including the present study, have shown that endoscopic hemostasis is the first indication for bleeding ulcers (37)(38)(39)(40)(41). The rate of hemostasis has been reported to be >95% in Japan, resulting in decreased mortality rates and indications for surgical treatment (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 51%
“…ESD has been accepted as a minimally invasive method for local resection for EGC with a negligible risk of lymph node metastasis [3] (Table 1). Although ESD is much less invasive than conventional open gastrectomy, complications have been reported to include hemorrhage in 5.5% of patients and delayed perforation in 0.45% [10,11].…”
Section: Minimally Invasive Treatment Methods For Early Gastric Cancermentioning
confidence: 99%